2023
DOI: 10.3390/jcm12113681
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Gelatinase-Associated Lipocalin (NGAL) in Patients with ST-Elevation Myocardial Infarction and Its Association with Acute Kidney Injury and Mortality

Abstract: Neutrophil gelatinase-associated lipocalin (NGAL) is an inflammatory biomarker related to acute kidney injury (AKI). Including 1892 consecutive patients with ST-elevation myocardial infarction (STEMI), in which NGAL was measured in 1624 (86%) on admission and in a consecutive subgroup at 6–12 h (n = 163) and 12–24 h (n = 222) after admission, this study aimed to evaluate the prognostic value of NGAL in predicting AKI and mortality. Patients were stratified based on whether their admission NGAL plasma concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Ahmet Avci (2020) [17] the study also found a similar result, with beta = 0.017 (p = 0.01) and dependent variables including age, hypertension, T2DM, dyslipidemia, smoking, sex, heart failure, and troponin. NGAL concentration could be biased due to the progression of chronic kidney disease (CKD) or Acute Kidney Injury as shown in the study by Højagergaard MA et al (2023) [24] . However, our study had strictly excluded the patients with kidney conditions, thus the outcome of our study had value meaning for clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Ahmet Avci (2020) [17] the study also found a similar result, with beta = 0.017 (p = 0.01) and dependent variables including age, hypertension, T2DM, dyslipidemia, smoking, sex, heart failure, and troponin. NGAL concentration could be biased due to the progression of chronic kidney disease (CKD) or Acute Kidney Injury as shown in the study by Højagergaard MA et al (2023) [24] . However, our study had strictly excluded the patients with kidney conditions, thus the outcome of our study had value meaning for clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Their results also demonstrated that NGAL was independently associated with cardiovascular outcomes and performed better than traditional inflammatory markers (e.g., C-reactive protein, leukocyte count, etc.). A second report by Højagergaard and colleagues included a cohort of >1600 patients with myocardial infarction [7]. They demonstrated that an NGAL plasma level above the median was an independent marker for severe AKI and all cause death within 30 days.…”
mentioning
confidence: 99%